Discontinuity Analysis Reveals Alternative Community Regimes During Phytoplankton Succession - Angeler, David G.; Allen, Craig R.; Twidwell, Dirac; Winder, Monika (Frontiers in Ecology and Evolution, 2019)
Phytoplankton develops recurring spring and summer blooms, a well-recognized model in plankton succession theory. We used a 5-year (2007-2011) plankton data set and utilized discontinuity analysis to assess the cross-scale biomass (carbon content) structure in the sampled plankton data, a surrogate of ecological resilience and regime shifts. We hypothesized that spring and summer blooms comprise alternative community regimes, manifested in distinct cross-scale structure between these blooms. We also hypothesized that cross-scale structure within blooms is stable, indicating resilient regimes of individual blooms. Both hypotheses were supported by our analyses. Results show that discontinuity analysis provides complementary information about phytoplankton community succession compared to traditional taxonomic studies. This highlights that traditional phytoplankton successional models and ecological resilience concepts are not mutually exclusive. Combined they offer a broader view of ecological dynamics that may help refine theoretical ecology which in turn can inform management.